Case report of anaesthetic management of neonate with large occipital encephalocele - Amit Sharma (International Journal of Medical Research and Review, 2019)
In the present case report, endotracheal intubation in a case of large occipital encephalocele presented for surgical excision was performed. As the management of airway even in a neonate is different and complex as compared to airway of old child and that of adult. It was challenging because of the difficulty in securing airway because of prone position in occipital encephalocele. The major concerns during the operation were to avoid premature rupture of the encephalocoele and to manage a possible difficult airway due to restricted neck movement and inability to achieve optimal position for intubation of the trachea. Continuous monitoring of patient was done during the surgery.